Ordered Completion for Logic Programs with Aggregates - Asuncion, Vernon; Zhang, Yan; Zhou, Yi (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
In this paper, we show that first-order logic programs with monotone aggregates under the stable model semantics can be captured in classical first-order logic. More precisely, we extend the notion of ordered completion for logic programs with a large variety of aggregates so that every stable model of a program with aggregates corresponds to a classical model of its enhanced ordered completion, and vice versa.